A Unified Model for the Coevolution of Galaxies and Their Circumgalactic Medium: The Relative Roles of Turbulence and Atomic Cooling Physics - Viraj Pandya; Drummond B. Fielding; Greg L. Bryan; Christopher Carr; Rachel S. Somerville; Jonathan Stern; Claude-André Faucher-Giguère; Zachary Hafen; Daniel Anglés-Alcázar; John C. Forbes (The Astrophysical Journal, 2023)
The circumgalactic medium (CGM) plays a pivotal role in regulating gas flows around galaxies and thus shapes their evolution. However, the details of how galaxies and their CGM coevolve remain poorly understood. We present a new time-dependent two-zone model that self-consistently tracks not just mass and metal flows between galaxies and their CGM but also the evolution of the global thermal and turbulent kinetic energy of the CGM. Our model accounts for heating and turbulence driven by both supernova winds and cosmic accretion as well as radiative cooling, turbulence dissipation, and halo outflows due to CGM overpressurization. We demonstrate that, depending on parameters, the CGM can undergo a phase transition (“thermalization”) from a cool, turbulence-supported phase to a virial-temperature, thermally supported phase. This CGM phase transition is largely determined by the ability of radiative cooling to balance heating from supernova winds and turbulence dissipation. We perform an initial calibration of our model to the FIRE-2 cosmological hydrodynamical simulations and show that it can approximately reproduce the baryon cycles of the simulated halos. In particular, we find that, for these parameters, the phase transition occurs at high redshift in ultrafaint progenitors and at low redshift in classical M _vir ∼ 10 ^11 M _⊙ dwarfs, while Milky Way–mass halos undergo the transition at z ≈ 0.5. We see a similar transition in the simulations though it is more gradual, likely reflecting radial dependence and multiphase gas not captured by our model. We discuss these and other limitations of the model and possible future extensions.